Challenges and Singularities of the Supervised Training in Teacher Formation in Social Sciences - Amurabi Oliveira (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
This paper aims to do a reflection on teacher formation in social sciences from a literature review of research conducted on this topic, considering the supervised training as a key in this process. Here we highlight particular aspects involved on stage in social sciences, on the one hand point to issues limiting the same, but on the other potentials indicate that this experience can bring to the educational process of the student. To do our analysis we consider both the actual route of Sociology in the school curriculum, this field of research is still incipient, as the debate on teacher formation in social sciences. We understand the supervised training as a fundamental element of teacher training, which therefore requires an accurate reflection within the field of knowledge that the future teacher will act. Finally, we note the significant gains that can be derived from the development of teaching practice in the field of Social Sciences.